Ratio-Entity Diagram: a tool for conceptual data modeling in Software Engineering (Research, Society and Development, 2021)
Data modeling is the main component of conceptual information in the database. Among the techniques for this modeling, Ratio-Entity (RE) is addressed in this work. The aimed is to address the main information about the entity-relationship model as a tool for conceptual data modeling. The Ratio-Entity Model, and especially the diagram, is an important tool during the development of systems, especially those more complex and difficult to visualize without further analysis. In addition, it is a conceptual model used in Software Engineering to describe the entities involved in a business domain, with their attributes and how they relate to each other. In general, it represents in an abstract way the structure that will have the application database. The database may contain several other entities, such as keys and intermediate tables, that may make sense in the context of relational databases.